Integrated multi-omics profiling to establish an IGFBP-based prognostic score for pancreatic ductal adenocarcinoma: unraveling prognostic biomarkers, immune microenvironment crosstalk, and therapeutic implications - Guan, Xiao; Mu, Yongrun; Jin, Xin; Wang, Chengfeng (Frontiers in Immunology, 2025)
BackgroundPancreatic ductal adenocarcinoma (PDAC) is accompanied by endocrine dysfunction, particularly involving dysregulation of the insulin and insulin-like growth factor (IGF) signaling pathways. Clinical manifestations such as hyperglycemia and insulin resistance are common and have been linked to aberrant expression of insulin-like growth factor-binding proteins (IGFBPs). However, the specific roles and mechanisms of IGFBP family genes in PDAC remain unclear.MethodWe conducted a multi-dimensional integrative analysis using publicly available PDAC cohorts, stratifying patients based on IGFBP gene expression profiles. A prognostic model was constructed to classify patients into risk groups. To explore the biological mechanisms underlying IGFBP involvement in PDAC, we further incorporated single-cell transcriptomic sequencing and spatial transcriptomic data to investigate the relationship between IGFBP expression and the tumor immune microenvironment.ResultOur prognostic model effectively stratified PDAC patients into distinct risk categories with significant survival differences. High-risk patients demonstrated specific IGFBP expression patterns associated with aggressive tumor biology. Single-cell and spatial transcriptomic analyses revealed that IGFBP family genes modulate immune cell infiltration and spatial immune heterogeneity within the tumor microenvironment.ConclusionThis study identified the IGFBP family genes as key modulators of PDAC progression and immune landscape remodeling. These findings supported the potential of IGFBP family genes as prognostic biomarkers and therapeutic targets, offering new insights into PDAC biology and opportunities for personalized treatment strategies.